Assessment of the long-term efficacy of a dengue vaccine against symptomatic, virologically-confirmed dengue disease by baseline dengue serostatus. Issue 19 (23rd April 2020) - Dayan, Gustavo H.; Langevin, Edith; Gilbert, Peter B.; Wu, Yukun; Moodie, Zoe; Forrat, Rémi; Price, Brenda; Frago, Carina; Bouckenooghe, Alain; Cortes, Margarita; Noriega, Fernando; DiazGranados, Carlos A.
Highlights: CYD-TDV efficacy was maintained for up to 6 years in seropositives aged ≥9 years. Persistent CYD-TDV efficacy was also observed in seropositives aged 6–8 years. CYD-TDV efficacy estimates were lower in seropositives aged <9 years than ≥9 years. CYD-TDV efficacy was null to modest in seronegatives aged ≥6 years. Abstract: CYD-TDV is a live, attenuated, tetravalent dengue vaccine licensed in 21 countries. We undertook a post-hoc analysis of the long-term efficacy of CYD-TDV during the surveillance expansion phase (SEP) of two Phase III studies (CYD14 in the Asia-Pacific region; CYD15 in Latin America). The SEP included approximately Year 5 and the entire Year 6 of follow-up after the first study injection. Vaccine efficacy against symptomatic virologically-confirmed dengue (VCD) was assessed by participant age (any age, ≥9, <9, 2–5, and 6–8 years at the time of the first injection) and baseline dengue serostatus using a case-cohort framework. Baseline dengue serostatus was estimated by several methods including logistic regression-based multiple imputation (MI) to predict PRNT50 with key predictor being Month 13 (M13) anti-non-structural protein (NS1) titers; superlearner-based imputation by targeted minimum loss based estimation (TMLE); and M13 anti-NS1 titer threshold 9 EU/mL (NS1 M13). There were 436 symptomatic VCD cases (CYD14: n = 360; CYD15: n = 76) during the SEP. Vaccine efficacy in seropositive participants aged ≥9 years was assessed by MI (47.9% [95% CI 19.4; 66.3]), TMLE (53.0% [95% CI 23; 71]), and NS1 M13 (52.4% [95% CI 30.8; 67.3]). Vaccine efficacy estimates were lower in seropositive individuals aged <9 years compared with individuals ≥9 years. Among seropositive individuals aged 2–5 and 6–8 years, vaccine efficacy across the different approaches for assessing serostatus ranged from between −25.7 to 36.9% and 44.4 to 64.7% during the SEP, respectively. In the pooled CYD14/15 data of seronegatives, vaccine efficacy was null to modest. In conclusion, CYD-TDV was shown to maintain efficacy against symptomatic VCD in seropositive participants aged ≥9 years up to six years after the first dose. Persistence of efficacy was also observed in seropositive participants aged 6–8 years.